THE EFFECTIVENESS OF USING COOPERATION READING AND COMPOSITION (CIRC) TOWARDS WRITING ACHIEVEMENT ACROSS STUDENTS’ SELF-EFFICACY AT SMAN 16 PEKANBARU - Wanda Azizah (InEJ: Indonesian Engagement Journal, 2022)
This study proves the Effectiveness of Using Cooperation Reading and Composition (CIRC) on Writing Achievement in All Students' Self-Efficacy. Researchers conducted this research at SMAN 16 Pekanbaru. The purpose of this research, the researcher wants to prove, is there any influence from CIRC in arousing students' self-efficacy in writing. Which is the population for this study namely eleventh grade students, and for the sample the students in class XI MIPA-1 and XI IPS-2. And for the sampling technique the researcher used a purposive method. The type of research that researchers use is quasi-experimental design. For this study, researchers will measure students' self-efficacy using the CIRC method in learning to write. And the results show that there is no effect of this method in increasing students' self-efficacy in learning to write.